Factors of Non-Muslim Customers Decision to Saving at Bank Syariah Indonesia (BSI) - Mulyani Rahman Soulisa; Rachma Indrarini (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam (e-Journal), 2023)
Islamic banks are not specific to the Muslim community, but non-Muslims also use them. The customer certainly has a reason for deciding the choice of using Islamic banks. This study aims to analyze decision factors of non-muslim customers saving at Bank Syariah Indonesia (BSI) Ambon. The research is associative quantitative type by using survey methods that distribute questionnaires for data collection. The sample taken with probability sampling technique is 98 non-muslim customers. Then the data is processed by confirmatory factor analysis techniques. In analyzing the data, the authors used the help of SPSS 26 software. The results of the study show that decision factors of non-muslim customers save at Bank Syariah Indonesia (BSI) Ambon is (1) promotion as the first and strongest factor with an Eigenvalue of 4,855; (2) perception as the second factor that has an Eigenvalue of 2,120; (3) service as the third factor that has an Eigenvalue of 1,275; (4) location as the fourth factor with an Eigenvalue of 1,136.